Implicature in The Devil Wears Prada Film - Lungguk Sitorus; Fauziah Nur; Lilis Lilis (Journal of Language, Literature and Teaching, 2019)
In the real life people cannot be separated from requirement to uselanguage for a communication. However not all utterances incommunication are clear, there are some utterances are implied.Speakers usually imply the meaning of an utterance when it isinsinuating another. This condition can be found in “The Devil WearsPrada” film. The design of this study used descriptive qualitativemethod because in this study the data are taken from statements andutterances in conversation in “The Devil Wears Prada” film. The dataof these researches were the sentences, speeches, dialogues used by thecharacters in the film. After finding and understanding the implicaturesexpressed in the film, the writer decided and identified the types ofimplicatures that mostly expressed by the speaker in the film. The writerfound implicatures used in “The Devil Wears Prada” film, they aregeneralized and particularized conversational implicature. In this filmmost of speakers used particularized conversational implicature.Speakers produce generalized conversational implicature when no specialknowledge in the context to calculate the additional conveyed meaning, itmeans that the participants in communication should obey thecooperative principle and the four maxim and speakers usedparticularized conversational implicature when they flout maxims ofcooperative principle because when speakers flout these maximsintentionally, they must observe the cooperative principle on deeperlevel or the hearers have difficulty to understand their attention. Bydoing this research, the writer finally understands what are implicaturesand its type. She also understands the reason of the speakers produceimplied meanings in their conversations. In the last, the writergives the suggestion to the next researchers who interested in doingresearch in the same area they must make it be more complete analysisand look for the other unique conversation in other situation to give anew implicatures style.Keywords: Implicature, Utterance, Particularized, Generalized, Context.